2019
DOI: 10.1002/lary.28269
|View full text |Cite
|
Sign up to set email alerts
|

Drain placement in thyroidectomy is associated with longer hospital stay without preventing hematoma

Abstract: Objective: To analyze the effect of drain placement on postoperative hematoma formation and other associated outcomes post-thyroid surgery in a large national cohort.Methods: This was a retrospective study that analyzed data from the 2016-2017 National Surgical Quality Improvement Program (NSQIP) public use files. Baseline characteristics and perioperative outcomes were compared between drain and no drain cohorts.Results: A total of 11,626 patients were included; 3281 had a drain placed intraoperatively and 83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…The difference in the rate of TT and CT between specialties may be attributable to variations in resident education and practice patterns. A NSQIP study showed that otolaryngologists were associated with a higher rate of drain placement in thyroidectomies relative to general surgeons; however, there was no significant difference in postoperative hematomas 32 . Another study determined that otolaryngologists in academic centers were more likely to use intraoperative nerve monitoring relative to general surgeons 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the rate of TT and CT between specialties may be attributable to variations in resident education and practice patterns. A NSQIP study showed that otolaryngologists were associated with a higher rate of drain placement in thyroidectomies relative to general surgeons; however, there was no significant difference in postoperative hematomas 32 . Another study determined that otolaryngologists in academic centers were more likely to use intraoperative nerve monitoring relative to general surgeons 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The drainage tube was found to be ineffective in preventing postoperative bleeding. Numerous studies, including a large-scale retrospective study ( 12 ), a randomized clinical trial ( 11 ), and meta-analysis ( 9 , 10 , 13 ), have proved drainage should not be routinely employed in COT. Drainage does not reduce the risk of complications like hemorrhage, recurrent laryngeal nerve palsy, and seroma, but increases the incidence of surgical site infection and hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al ( 14 ) and Chen et al ( 26 ) reported the drainage time with 2.7 ± 0.6 days and 4.3 ± 0.9 days, respectively, and the hospital stay with 6.4 ± 1.2 days and 6.4 ± 0.8 days, respectively. Previous studies revealed that drain placement is associated with more extended hospital stay in COT ( 9 12 ), and the application of negative pressure drainage is an important reason that interferes with lymph tube sealing and increases drainage volume ( 31 ). In the present study, with no drainage applied, the total hospital stay significantly reduced from 4.78 ± 1.33 days to 2.40 ± 0.71 days ( P < 0.001), and postoperative hospital stay decreased considerably from 2.15 ± 0.36 days to 2.04 ± 0.19 days ( P = 0.048).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 A study by Maroun et al using ACS NSQIP data also demonstrated that drain use does not reduce hematoma risk and is associated with a longer LOS. 30 The differences in postoperative complications between the VSD and non-VSD groups may be attributable to the biomechanics of each method. VSDs that are used for thyroidectomies can be classified into advanced bipolar systems, such as LigaSure, or ultrasonic devices, such as the harmonic scalpel.…”
Section: Discussionmentioning
confidence: 99%